2020
DOI: 10.1371/journal.pone.0240454
|View full text |Cite
|
Sign up to set email alerts
|

Cooling-mediated protection from chemotherapy drug-induced cytotoxicity in human keratinocytes by inhibition of cellular drug uptake

Abstract: Chemotherapy-induced alopecia (CIA) represents the most distressing side-effect for cancer patients. Scalp cooling is currently the only treatment to combat CIA, yet little is known about its cytoprotective effects in human hair follicles (HF). We have previously established in vitro human keratinocyte models to study the effects of taxanes and anthracyclines routinely-used clinically and reported that cooling markedly-reduced or even completely-prevented cytotoxicity in a temperature dependent manner. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…HCT116 cells were seeded at 1 × 10 4 cells/well in 96-well plates and treated with 10-20 ng/mL of human recombinant killer TRAIL™ (Enzo, Exeter, UK) in the absence or presence of anti-FasL mAb NOK-1, anti-TRAIL mAb RIK-2 or control isotype Control IgG (all at 10 µg/mL) [ 13 ], alongside untreated control cultures, for 24 h. Cell viability was then determined using the CellTiter 96 ® AQueous One cell proliferation assay (Promega, Southampton, UK) by addition of 20 μL CellTiter reagent to each well and incubation at 37 °C for 4 h. Absorbance was measured using a FLUOstar OPTIMA (BMG Labtech, Bucks, UK) at 492 nm and percentage (%) Cell Viability calculated as previously described [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…HCT116 cells were seeded at 1 × 10 4 cells/well in 96-well plates and treated with 10-20 ng/mL of human recombinant killer TRAIL™ (Enzo, Exeter, UK) in the absence or presence of anti-FasL mAb NOK-1, anti-TRAIL mAb RIK-2 or control isotype Control IgG (all at 10 µg/mL) [ 13 ], alongside untreated control cultures, for 24 h. Cell viability was then determined using the CellTiter 96 ® AQueous One cell proliferation assay (Promega, Southampton, UK) by addition of 20 μL CellTiter reagent to each well and incubation at 37 °C for 4 h. Absorbance was measured using a FLUOstar OPTIMA (BMG Labtech, Bucks, UK) at 492 nm and percentage (%) Cell Viability calculated as previously described [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative detection of NHEK and HaCaTa cell proliferation was performed using the CellTiter 96 ® AQueous One Solution Cell Proliferation Assay (Promega, Southampton, United Kingdom), as recommended by the manufacturer and absorbance determined by spectrophotometric measurements at 492 nm using a FLUOstar OPTIMA (BMG Labtech, Bucks, United Kingdom). Following normalisation using medium-only 'blank' wells, cell proliferation was calculated as described previously (Dunnill et al, 2020).…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%
“…Scalp cooling therapy (SCT) has gained traction over the past decade as a method to decrease CIA, based on the concept of scalp hypothermia reducing blood ow in the scalp to 20-40% of the usual rate by vasoconstriction. This decreases the concentration of chemotherapy reaching the scalp [9], and also metabolic rate of the follicle cells and drug uptake [10,11]. In vivo studies have shown that cooling protects human keratinocytes from chemotherapy-induced toxicity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This decreases the concentration of chemotherapy reaching the scalp [9], and also metabolic rate of the follicle cells and drug uptake [10,11]. In vivo studies have shown that cooling protects human keratinocytes from chemotherapy-induced toxicity [11,12]. Various scalp cooling systems including Paxman and Dignicap have been shown to be effective in reducing hair loss in 50-68% of patients [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%